The roles of histone methylation in the regulation of abiotic stress responses in plants - Lei Shi; Xiaoyun Cui; Yuan Shen (Plant Stress, 2024)
Abiotic stress greatly threaten plants’ growth and ultimately impact crop productivity. Plants have evolved sophisticated regulatory mechanisms to cope with stressful conditions, including undergoing physiological changes through genetic and epigenetic regulation of gene expression. Histone methylation takes an essential part in epigenetic regulation of the expression of numerous genes in plant response to abiotic stresses. In this review, we summarize the recent progress on the regulation of histone methylation in plant response to abiotic stress, including drought, high salinity, high temperature, and cold. We also discuss the roles of histone methylation in the formation of plant stress memory, as well as the metabolic regulation of histone methylation under abiotic stress in plants. We posit that a comprehensive understanding of the molecular mechanisms and functional roles of histone methylation in abiotic stress responses will accelerate plant breeding, improve stress resistance and substantially enhance biomass and crop yield.